2010
DOI: 10.1097/hjr.0b013e328333ede6
|View full text |Cite
|
Sign up to set email alerts
|

Criterion-related validity of the short International Physical Activity Questionnaire against exercise capacity in young adults

Abstract: IPAQ-Gr was tested against exercise capacity and showed acceptable validity properties in Greek young adults. Total and vigorous weekly PA expenditure were well associated with exercise capacity, presenting significant validity correlations against maximal treadmill time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
203
0
10

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 208 publications
(221 citation statements)
references
References 41 publications
8
203
0
10
Order By: Relevance
“…With fitness measures (VO2max, maximum treadmill time, and 6-minute walk test reported in the lower section of Table 2), the correlations with the IPAQ-SF total activity level were small in four of the five studies (range of ρ = 0.16 [33] to 0.36 [37], median = 0.30). Only one study validated the IPAQ-SF against anthropometric measures, which reported a small correlation between the IPAQ-SF and body fat percentage (ρ = -0.19 [44], not shown in any tables).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…With fitness measures (VO2max, maximum treadmill time, and 6-minute walk test reported in the lower section of Table 2), the correlations with the IPAQ-SF total activity level were small in four of the five studies (range of ρ = 0.16 [33] to 0.36 [37], median = 0.30). Only one study validated the IPAQ-SF against anthropometric measures, which reported a small correlation between the IPAQ-SF and body fat percentage (ρ = -0.19 [44], not shown in any tables).…”
Section: Resultsmentioning
confidence: 99%
“…Fifteen studies used an objective device that monitored body motion [17-20,25,29-32,35,38-40,42,43], two examined scores against a physical fitness measure [37,41], four used both an objective device and a physical fitness measure [23,33,34,36] and one compared findings against anthropometric measures [44] (Tables 2 and 3). Of those reporting data from motion-sensing devices, one of them used the actometer, two used a pedometer, and fifteen used an accelerometer.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations